Food choice motivations: Profiling low-carbohydrate, high-fat dieters. (1st October 2019) - Clarke, Chantelle; Best, Talitha
Abstract: We sought to determine the motivational profile of low-carbohydrate, high-fat (LCHF) dieters compared to other-dieter and non-dieter groups, in terms of both absolute food choice motivations (FCMs) and relative FCMs (how one motivation is prioritised against others). Participants ( N = 330, 287 female, 43 male) completed a 12-scale food choice questionnaire online. Results showed that all three groups prioritised the FCM of health highly. Differences between the dietary groups (adjusting for age) showed that the "LCHF diet" and "other-diet" group rated FCM's weight control and natural content (absolute and relative motivation scores) significantly higher than those in the "no-diet" group. Whereas, FCM's price and convenience (absolute and relative motivation scores) were rated significantly lower than the "no-diet" group. Importantly, FCM Natural content was the top priority for the "LCHF diet" group, and its level of importance significantly differed from the "other-diet" group, who scored natural content significantly lower in both absolute and relative terms. In contrast, the "LCHF diet" group scored significantly lower on relative animal welfare as compared to both other groups. The pattern of both absolute and relative food choice motivation scores between each group is discussed. These results show a novel profile of differences for absolute and relative FCMs between LCHF dieters, other-dieters and non-dieters. Highlights: We assessed differences in the food choice motivational profile of LCHF dieters, other dieters and non-dieters. The use of relative motivations can provide further insight into food choice/dieting behaviour. Health was identified as an important relative motivation for food choice for all groups. Food choice motivations of natural content, health and weight control defined the LCHF diet group.